Cyrtodactylus kunyai (Squamata: Gekkonidae), a new cave-dwelling Bent-toed Gecko from Loei Province, northeastern Thailand - Pauwels, Olivier S.g.; Sumontha, Montri; Keeratikiat, Kaweesak; Phanamphon, Eakarit (Zootaxa, 2014)
We describe a new cave-dwelling Cyrtodactylus from Suan Hin Pha Ngam, Nong Hin District, Loei Province, northeastern Thailand, characterized by a maximal known snout-vent length of 87.9 mm, a banded dorsal pattern with a medially interrupted nuchal loop and four or five brown bands between nuchal loop and hind limb insertions and three bicolored band interspaces between limbs insertions, a dark orangeish iris, a continuous series of enlarged femoro-precloacal scales with 5–6 femoral pores on each side separated by a diastema from 3 precloacal pores in males (no pores in females), 19 irregularly arranged dorsal longitudinal tubercle rows at midbody, 34 ventral scale rows between ventrolateral skin folds, transversely enlarged subcaudal plates, and no precloacal groove.